2012
DOI: 10.5851/kosfa.2012.32.5.659
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Marbling Score on Carcass Grade Factors, Physico-chemical and Sensory Traits of M. Longissimus Dorsi in Hanwoo

Abstract: The objective of this research was to investigate the effect of marbling scores on carcass grade factors, physico-chemical and sensory traits of Hanwoo. Data used in this study were collected from 73,316 carcasses obtained at the Nonghyup Seoul slaughterhouse in 2009 and 271 cuts of M. longissimusdorsi were analyzed to estimate beef qualities. As the marbling scores increased, backfat thickness was linearly increased (p<0.05) in cows (9.51 mm-14.69 mm) and steers (8.71 mm-14.23 mm). As the marbling scores incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
2
4
0
Order By: Relevance
“…The effect of TDN level on the physicochemical characteristics of the longissimus muscle was not significant, and the shear force and physical characteristics (e.g., elasticity, cohesiveness, adhesiveness, and chewiness) of the longissimus muscle were relatively low in the T2 compared to the other treatments. Previous studies have shown no differences among the different grades in WHC, cooking loss, moisture, and crude protein content (Lee et al, 2012), which were similar results to those of the present study.…”
Section: Resultssupporting
confidence: 92%
“…The effect of TDN level on the physicochemical characteristics of the longissimus muscle was not significant, and the shear force and physical characteristics (e.g., elasticity, cohesiveness, adhesiveness, and chewiness) of the longissimus muscle were relatively low in the T2 compared to the other treatments. Previous studies have shown no differences among the different grades in WHC, cooking loss, moisture, and crude protein content (Lee et al, 2012), which were similar results to those of the present study.…”
Section: Resultssupporting
confidence: 92%
“…The significant variables in discrimination were moisture, WHC, shear force, and backfat thickness in order. This result is consistent with the fact that the marbling score differs by the moisture contents [5,23], and the shear force is a determinant factor affecting MQG [24]. When 24 post-deboning variables were applied, the total discrimination accuracy was 59.7% and accuracy was 70.6%, 53.0%, 43.6%, and 71.5% for 1+, 1, 2, and 3 MQG, respectively ( Table 3).…”
Section: Distribution Of Quality Grade By Carcass Yield Indexsupporting
confidence: 83%
“…The significant variables of pre-deboning were moisture, shear force, and cold carcass weight and classified bulls by meat quality of 1, 2, and 3 with an accuracy of 50%, 62.8%, and 90.2%, respectively. The high accuracy observed in bulls seemed that bulls had more moisture content [17,23], which significantly affected meat quality compared to others [6,12,23]. The significant variables of post-deboning data were body fat, rip, striploin, tail, hanging tender, top round, hind-shank, bone, hind-leg bone, and doggy bone.…”
Section: Distribution Of Quality Grade By Carcass Yield Indexmentioning
confidence: 96%
“…A higher amount of intramuscular fat (marbling) in beef increases the product’s tenderness and flavor, which in turn leads to greater consumer satisfaction ( Lee et al, 2017 ). Hence, a number of attempts have been made to improve the tenderness and flavor of beef by controlling intrinsic and/or extrinsic factors ( Choe et al, 2019 ; Lee et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%